9B.04: DOES CONTRALATERAL SUPPRESSION AT ADRENAL VENOUS SAMPLING PREDICT OUTCOME FOLLOWING UNILATERAL ADRENALECTOMY FOR PRIMARY ALDOSTERONISM? A RETROSPECTIVE STUDY. (June 2015) - Wolley, M.; Ahmed, A.; Gordon, R.; Stowasser, M.
Abstract : Objective: In primary aldosteronism (PA), adrenal vein sampling (AVS) distinguishes unilateral and bilateral disease. In AVS aldosterone/cortisol ratios (A/F) correct aldosterone concentration for dilution from non-adrenal blood. Comparisons are then made between left, right and peripheral A/F ratios. Criteria for interpretation however vary widely. Most units use the lateralisation index (LI); A/F dominant: A/F non-dominant with a cut-off value varying from 2–4 for unilateral disease. We use the criteria of 'contralateral suppression' (CS) defined as: A/F (adrenal) < = A/F (peripheral) on the unaffected side, combined with a ratio >=2 times peripheral on the affected side. Patients with one side clearly dominant but without CS are however sometimes offered surgery. The importance of CS in AVS interpretation is unclear, and we therefore performed a retrospective study to determine if CS in unilateral PA was associated with blood pressure (BP) and biochemical outcomes. Design and method: All patients who underwent unilateral adrenalectomy for PA at the Princess Alexandra Hospital between 2000 and 2014 were included if AVS was successful (cortisol (adrenal): cortisol (peripheral) >=3 bilaterally), if the LI was >=2 and if they had >=6 months of post-operative follow up. Cases were reviewed for BP and biochemical outcomes with respect to the presence and degree of CS. Results: 80 patients were suitable for review, and 66 had CS. Baseline characteristics were similar. At post-operative follow up, those with CS had a lower systolic BP (SBP; 128mmHg vs. 144mmHg p=0.001), a greater proportion with cure or improvement of hypertension (96% vs 64%, p = 0.0034), a greater proportion with biochemical cure of PA on fludrocortisone suppresion testing (43/49 (88%) vs 4/9 (44%), p = 0.002) and were on a lower number of antihypertensive medications (0 vs 1.5, p = 0.0032). In a multivariate model, the degree of CS and pre-operative SBP were independently associated with post-operative SBP, but LI, gender and age were not. Conclusions: In this study the presence of CS correlated with good BP and biochemical outcomes from surgery. This suggests that CS should be a factor in deciding whether to offer surgery for treatment of PA.